Penerapan Artificial Intellegence (AI) Dalam Perkembangan Cyber Notary di Era Transformasi Digital - Setyawan, Angelina Regita Kerin; Ali, Moh.; Sari, Nuzulia Kumala (Acten Journal Law Review, 2025)
A notary is a public official who, in carrying out their duties, refers to the Notary Position Law, which stipulates that the creation of deeds must be done face to face with clients. However, in the provisions of the Notary Law itself, Article 15 Paragraph (1) letter m provides that cyber notaries can be implemented. This research aims to assess the application of artificial intelligence (AI) in the development of cyber notaries in the era of digital transformation and to examine to what extent AI will support or replace the role of notaries as public officials. This study uses normative legal research with a legislative and conceptual approach through literature studies that are analyzed descriptively. The results of this study indicate the position of AI in the Notary Position is only as a supporting tool, not as a substitute for the notary position, because AI cannot legally replace the role of a notary, regarding the position of AI there are also no clear norms in the laws and regulations. So the position of AI in cyber notary is only as a supporting tool for Notaries which provides many conveniences for notaries in carrying out their duties. The application of AI as part of cyber notary by optimizing AI performance so that notaries can work more effectively and efficiently. With the existence of legal provisions that are in line with the application of AI in cyber notary, it will certainly make it easier for notaries to carry out their duties, in addition to the guarantee of electronic storage of notary protocols, there also needs to be legal provisions with the guarantee of client data security.